Análise de livros didáticos conforme as considerações do Programa Nacional do Livro Didático : estatística e probabilidade - Santos, Danilo Messias Nascimento e (2016)
The National Textbook Program (PNLD) aims to choose, through a Public Notice, textbooks collections to be used in classrooms of public primary education and prepare, at the end of the procedure, a Guide of textbooks for teachers to choose them according to the considerations and reviews elaborated. So, by the importance of Statistics and Probability, which are applied in daily life in different situations, and because in the Guide there are predatory and classificatory aspects asked in the Public Notice, in a more analytical way for each collection, we investigated in this research if the collections approved in 2015 PNLD contain the recommendations of the program for these subjects. For this, in a first stage, we selected five collections of high school (appointed by L1, L2, L3, L4 and L5) that were adopted by public schools in Sergipe and evaluated according to the content analysis technique, making categories, according to the considerations of the Guide. In order to close a cycle, that connects PNLD – Textbook –Teacher, we also researched, in a second stage, the opinion of some mathematics teachers who teach in high school and are studying master's degree at the Federal University of Sergipe on, essentially, the choice of textbooks and the way they approach the statistics. For this, we applied a questionnaire and used the descriptive and statistical analysis technique as well as the content analysis. Thus, among the categories in the first phase, there are the Textbooks Presentation and the contents distribution, in which we highlighted our views about the cover, title and we verified quantitatively how they distributed the contents of Statistics and Probability. Moreover, we observed the Teaching and Learning Methodology, and we found out that all the collections used an approach that supports a passive learning, with no moment for reflection, except for specific sections. Concerning to the use of technologies, some textbooks bring examples to be used with the contents of Data Analysis area, such as software and calculator tutorials use. Another examined feature was the contextualization, defined by the Guide under the aspects of social practices and the history of mathematics. In the first, we note the inclusion in all collections through sections or exercises and in the second we realized that only one collection brings historical figures of Statistics. Moreover, few books discuss the historical evolution of the concepts and the social, economic and scientific reasons which led to the advancement of mathematics. The last category of this stage was the specific topics of Statistics and Probability, which we highlighted as the data collection stimulus or if the textbook uses a different definition of probability, beyond the classic. In the second stage of the investigation, more practical, the analysis showed that the respondents declare to know the PNLD, but they are not guided by the guide to choose collections that they will use in the classroom. The approach of statistics in textbook is considered partially satisfactory, with summarized contents and little stimuli to data collection projects. Therefore, we reflect if the federal funds earmarked for this program are being undervalued and if the collections are even being improved in accordance with the National Curriculum Guidelines, which is the basis of inquiry for the preparation of the Textbook Guide.